Juridical Analysis of Sanctions On The Criminal Action Of Narcotics Abuse Goal I According To Law No. 35 Of 2009 - Sukhebi Mofea; Rommy Utama; Wahyu Diana (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
Research objectives to find out and analyze; Determination of criminal sanctions against the main perpetrators of class 1 narcotics abuse. Judges' considerations in imposing criminal penalties on class 1 narcotics abuse based on decisions (No2166/pid.sus/2018/PN. Research method; with a descriptive qualitative approach that describes phenomena and incidents in the field at the research location. Data collection techniques: Through field research, library research, and interviews with parties handling cases such as prosecutors, judges, lawyers, and suspects. Conclusion: Application of criminal sanctions against the main perpetrators of class narcotics abuse 1. Application of sanctions to the abuse of narcotics class I committed by Defendant Kurniawan in Decision Number 2166/2018/PN.Tng, the authors conclude that the application of sanctions, in this case, was the wrong target or the wrong person. The Judge's considerations in imposing a criminal offense against narcotics abuse class 1 based on the decision (No 2166/2018/PN.Tng). It is legal and convincing that the decision is correct.